Quality of attached and detached-ripened tomatoes cv Gigante Kadá - Carvalho, Vânia Déa de; Souza, Sara Maria Chalfoun de; Chitarra, Maria Isabel Fernandes; Cardoso, Diva Aparecida Moutinho; Chitarra, Adimilson Bosco (Pesquisa Agropecuaria Brasileira, 2014)
The following variables were determined: total soluble solids and alcohol insoluble solids contents, total titratable acidity, soluble solids acidity ratio, reducing sugars. C total vitamin and total carotenoids values on tomatoes (Lycopersicon esculentum Mill) of Gigante Kadá cultivar. These observations were made in different periods of ripening of attached and detached fruits to determine the influence of the type and period of ripening on the fruit quality. It was observed that: a) in both types of ripening the ripened fruit had higher total and soluble solids, reducing sugars, and total carotenoid content than the unripened ones; b) in the attached-ripened fruits, the titratable acidity reached a peack at the beginning of the ripening period; and in the detached-ripened fruits this peak reached in the green-ripe ones; c) the alcohol insoluble solids and C vitamin content kept the same values during the ripening process; d) the attached-ripened fruits presented higher C total vitamin contents.